Intermediate-grade meningeal melanocytoma in a 19 months old child with difficulties in differential diagnosis and management - (:unkn) unknown (My University, 2021)
Intermediate-grade meningeal melanocytomas (IGM) are rarely reported tumors and has not been reported in childhood yet. They are spaculated to have more agressive clinical behavior and their best management options has not been defined. Here we report a 19 months old child being the first case in English literature having IGM. Pre-operative diagnosis was confusing since patient history was unclear and radiological features resembled a growing skull fracture or a subtype of congenital parietal bone agenesis. An area of 5x7 cm dura was found to be dark grey and black in colour and excised but the operation was complicated with brain edema and swelling, and a second operation for reconstruction and dural repair was needed. Of the 16 patients reported in adults, 14 showed a high recurrence rate without adjuvan radiotherapy, and 2 did not showed recurrence with adjuvan radiotherapy. Our patient did not have adjuvan radiotherapy since he was just 19 months old at the time his diagnosis and did not show recurrence until now at 24 months of follow-up. Close monitoring with radiological imaging is of paramount importance.